Studie på beteendeförändringar hos katt efter behandling av Feline Odontoclastic Resorptive Lesion (FORL) - Naffah, Christopher (SLU/Dept. of Animal Environment and Health (until 231231), 2005)
Feline odontoclastic resorptive lesion (FORL) is a tooth disease affecting both domestic and wild cats. Although FORL was described as early as the 1920´s, the etiology is still unclear. Several hypotheses have been presented but different studies have obtained contradictory results, and today there is no generally accepted etiology. Teeth affected by FORL are characterized by root resorption with progressive destruction of the tooth structure and alveolar bone as a consequence of clast cell activity. The disease is considered very painful when reaching a certain stage. This might lead to an altered behaviour of affected cats. Assessing chronic pain in animals is difficult and a careful interview of the owner, concerning their animal´s behaviour, is of great importance. The aim of this study is to see if there are any behavioural changes in cats after FORL treatment as a result of removal of pain. The results in this study suggest that cats show reduced pain behavior after treatment. However the test group in this study is to small for statistical calculations.